Vitamin D Exerts Significant Antitumor Effects by Suppressing Vasculogenic Mimicry in Breast Cancer Cells - Bajbouj, Khuloud; Al-Ali, Abeer; Shafarin, Jasmin; Sahnoon, Lina; Sawan, Ahmad; Shehada, Ahmed; Elkhalifa, Walaaeldin; Saber-Ayad, Maha; Muhammad, Jibran Sualeh; Elmoselhi, Adel B.; Guraya, Salman Y.; Hamad, Mawieh (Frontiers in Oncology, 2022)
Background: Numerous clinical and experimental observations have eluded the substantial anti-neoplastic role of vitamin D against breast cancer (BC), primarily by inducing apoptosis and by affecting metastasis. Tumor progression and resistance to chemotherapy have been linked to the vasculogenic mimicry (VM), which represents the endothelial-independent formation of microvascular channels by cancer cells. However, the effect of vitamin D on VM formation in breast cancer has not been thoroughly investigated. This study examined the impact of 1α,25-dihydroxyvitamin D3 (calcitriol), the active form of vitamin D, on the expression of major factors involved in BC migration, invasion, and VM formation. Experimental methods: Publicly available transcriptomic datasets were used to profile the expression status of the key VM markers in vitamin D-treated BC cells. The in-silico data were validated by examining the expression and activity of the key factors that are involved in tumor progression and MV formation in hormone positive MCF-7 and aggressive triple‐negative MDA-MB-231 BC cells after treatment with calcitriol. Results and Discussions: The bioinformatics analysis showed that tumor VM formation-enriched pathways were differentially downregulated in vitamin D-treated cells when compared with control counterparts. Treatment of BC cells with calcitriol resulted in increased expression of tissue inhibitors of metalloproteinases (TIMPs 1 and 2) and decreased content and gelatinolytic activity of matrix metalloproteinases (MMPs 2, and 9). Furthermore, calcitriol treatment reduced the expression of several pro-MV formation regulators including vascular endothelial growth factor (VEGF) and tumor growth factor (TGF-β1), and Amphiregulin. Eventually, this process resulted in a profound reduction in cell migration and invasion following the treatment of BC cells with calcitriol when compared to the controls. Finally, the formation of VM was diminished in aggressive triple‐negative MDA-MB-231 cancer cell line after calcitriol treatment. Conclusion: Our study findings establish the significant anti-tumor effects of vitamin D in BC cells by inhibiting and curtailing their potential of VM formation.